2001
DOI: 10.1161/01.res.88.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Slowing and Sudden Arrhythmic Death in Mice With Cardiac-Restricted Inactivation of Connexin43

Abstract: Abstract-Cardiac arrhythmia is a common and often lethal manifestation of many forms of heart disease. Gap junction remodeling has been postulated to contribute to the increased propensity for arrhythmogenesis in diseased myocardium, although a causative role in vivo remains speculative. By generating mice with cardiac-restricted knockout of connexin43 (Cx43), we have circumvented the perinatal lethal developmental defect associated with germline inactivation of this gap junction channel gene and uncovered an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
528
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 608 publications
(566 citation statements)
references
References 55 publications
35
528
0
Order By: Relevance
“…Germline deletion of the Cx43 gene in mice leads to perinatal lethality due to developmental cardiac malformation 30 . In contrast, mice with cardiac-restricted inactivation of Cx43 are viable; however, they develop ventricular tachyarrhythmias leading to sudden cardiac death within 2 months 50,51 . Several mutations in Cx43 have previously demonstrated serious conduction abnormalities both in mouse models and in human patients 47,[52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…Germline deletion of the Cx43 gene in mice leads to perinatal lethality due to developmental cardiac malformation 30 . In contrast, mice with cardiac-restricted inactivation of Cx43 are viable; however, they develop ventricular tachyarrhythmias leading to sudden cardiac death within 2 months 50,51 . Several mutations in Cx43 have previously demonstrated serious conduction abnormalities both in mouse models and in human patients 47,[52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cx43, which contributes to intercellular communication and electrical coupling, is the principal component of ventricular gap‐junction proteins. Genetically engineered Cx43‐deficient (Cx43 +/− or Cx43 −/− ) mice have been reported to be markedly susceptible to ischemia‐induced ventricular tachycardia 36, 37, 38. Ando et al39 reported that increased vagal tone could prevent the loss of Cx43 during acute MI and thus exert antiarrhythmogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…They found decrease in connexin43 levels in acute state of volume overload HF but when compensatory hypertrophy developed, the amount of connexin43 seemed to normalize (Goldfine et al, 1999). In any case, the absolute levels of connexin43 have to be decreased over 50% to induce significant physiological phenotype per se, as indicated by apparent normality of connexin43 heterozygous mice as well as ventricular arrhythmias leading to sudden cardiac death observed in myocardium-restricted null animals (Gutstein et al, 2001). In this respect, the 60% decreased in total amount of connexin43 found in our Western blot seems biologically sufficiently significant to form (together with changes in cell shape) a proarrhythmogenic substrate, as ventricular arrhythmias were recorded in $10% of our HF animals.…”
Section: Discussionmentioning
confidence: 99%